Regional distribution and kinetics of [18F]fluciclovine (anti-[18F]FACBC), a tracer of amino acid transport, in subjects with primary prostate cancer - Sörensen, Jens; Owenius, Rikard; Lax, Michelle; Johansson, Silvia (European journal of nuclear medicine and molecular imaging, 2013)
Purpose [ 18 F]Fluciclovine (anti-[ 18 F]FACBC) is a synthetic amino acid developed for PET assessment of the anabolic component of tumour metabolism in clinical routine. This phase 1 trial evaluated the safety, tracer stability and uptake kinetics of [ 18 F]fluciclovine in patients. Methods Six patients with biopsy-proven prostate cancer were investigated with 3-T MRI and PET/CT. All underwent dynamic [ 18 F]fluciclovine PET/CT of the pelvic area for up to 120 min after injection of 418 ± 10 MBq of tracer with simultaneous blood sampling of radioactivity. The kinetics of uptake in tumours and normal tissues were evaluated using standardized uptake values (SUVs) and compartmental modelling. Results Tumour deposits as defined by MRI were clearly visualized by PET. Urine excretion was minimal and normal tissue background was low. Uptake of [ 18 F]fluciclovine in tumour from the blood was rapid and the tumour-to-normal tissue contrast was highest between 1 and 15 min after injection with a 65 % reduction in mean tumour uptake at 90 min after injection. A one-compartment model fitted the tracer kinetics well. Early SUVs correlated well with both the influx rate constant ( K 1 ) and the volume of distribution of the tracer ( V T ). There were no signs of tracer metabolite formation. The product was well tolerated in all patients without significant adverse events. Conclusion [ 18 F]Fluciclovine shows high uptake in prostate cancer deposits and appears safe for use in humans. The production is robust and the formulation stable in vivo. An early imaging window seems to provide the best visual results. SUV measurements capture most of the kinetic information that can be obtained from more advanced models, potentially simplifying quantification in future studies.